Mechanical characterization and identification of material parameters of porcine aortic valve leaflets. (December 2020) - Laville, Colin; Pradille, Christophe; Tillier, Yannick
Abstract: The ideal artificial heart valve does not exist yet. Understanding of mechanical and structural properties of natural tissues is necessary to improve the design of biomimetic aortic valve. Besides these properties are needed for the finite element modeling as input parameters. In this study we propose a new method combining biaxial tests and digital image correlation. These tests are carried out on porcine aortic valves. In this work, we use a modified version of the HGO (Holzapfel-Gasser-Ogden) model which is classically used for hyper-elastic and anisotropic soft tissues. This model can include fiber orientation. The identification of HGO model parameters can be determined using experimental data and two different protocols. One protocol is based on the identification of collagen fibers orientation as well as the mechanical parameters. The second one, is based on a complementary experiment to determine orientation (confocal laser scanning microscope). Both lead to determine different sets of material parameters. We show that the model is more likely to reproduce the actual mechanical behavior of the heart valves in the second case and that a minimum of three different loading conditions for the biaxial tensile tests is required to obtain a relevant set of parameters. Graphical abstract: Image 1 Highlights: Several loading protocols are necessary to measure aortic valves mechanical behavior. A modified version of the HGO model gives relevant results. Both biaxial tensile test data and confocal structural information are required. Our set of model parameters allows to model every loading conditions.